2010
DOI: 10.1021/jp909127a
|View full text |Cite
|
Sign up to set email alerts
|

DNA Binding Ability and Hydrogen Peroxide Induced Nuclease Activity of a Novel Cu(II) Complex with Malonate as the Primary Ligand and Protonated 2-Amino-4-picoline as the Counterion

Abstract: The DNA binding property of a Cu(II) complex, viz., [Cu(mal)(2)](picH)(2).2H(2)O, (mal)(2) = malonic acid, picH = protonated 2-amino-4-picoline, has been investigated in this study. The binding of this complex with plasmid and chromosomal DNA has been characterized by different biophysical techniques. From the absorption and fluorescence spectroscopic studies, it has been observed that the said copper complex binds strongly with pUC19 plasmid and CT DNA with a binding affinity of 2.368 x 10(3) and 4.0 x 10(3) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 66 publications
0
9
0
Order By: Relevance
“…Protein/peptide interactions with polymers and nanoparticles Nucleic acid interactions other than with proteins Enzyme activity and kinetics Other unclassified studies (including, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Protein/peptide interactions with polymers and nanoparticles Nucleic acid interactions other than with proteins Enzyme activity and kinetics Other unclassified studies (including, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…36 Our previous in vitro study showed that the complex interacts with DNA as a partial intercalator as well as a partial minor groove binder. 1 However, in the present work, we have provided evidence that the complex can induce death in HeLa, HepG2 and THP1 cells in a dose and time dependent manner. The mechanism of cell death is coupled with the induction of mitotic catastrophe (MC) followed by apoptosis.…”
Section: Introductionmentioning
confidence: 49%
“…1) having established supramolecular structure in the solid state 36 has been shown to bind with DNA. 1 In the present study, the possible cytotoxicity of the complex and its mechanism of action have been explored on the human cell lines. Clonogenic survival as well as MTT assay gave us initial impression about the cytotoxic effect induced by the complex.…”
Section: Resultsmentioning
confidence: 99%
“…The experiment followed a technique that had already been reported in the literature [18]. It's well de ned that there has been large accumulation of H 2 O 2 in several tumor tissues [19] and it was reported earlier that some complexes like Cu, and Pt containing compounds [20] induced DNA cleavage activity in the presence of reducing agents like H 2 O 2 , we also explored the possible nuclease activity of P5, and P16 in the presence of H 2 O 2 .…”
Section: Gel Electrophoresis Studymentioning
confidence: 99%